Re-use of wind turbine blade for construction and infrastructure applications. Issue 1 (October 2020) - André, A; Kullberg, J; Nygren, D; Mattsson, C; Nedev, G; Haghani, R
Abstract: To achieve a more resource-efficient society with a future with reduced carbon dioxide emissions, new technological challenges must be dealt. One way to reach a more sustainable world is to start re-using end-of-life structures and waste and give them a 'Second Life" with a new function in the society. As composite structures are lightweight, strong, stiff and durable materials, there is great potential to re-use decommissioned composite for new resource-efficient solutions in the building and infrastructure sector. The present paper investigates innovative solutions in re-using wind turbine blades as elements in new bicycle and pedestrian bridge designs. Several conceptual bridge designs where wind blades utilized as load bearing elements were developed and studied. The main design requirements for pedestrian bridges were considered and assumptions regarding wind blades quality and their mechanical properties addressed based on interviews with industries working with wind turbine blades repair and recycling. The aim of this paper is to contribute to a sustainable use of fibre reinforced polymer (FRP) waste and at the same time provide a more cost-effective FRP bridges. In a larger perspective, the authors would like to highlight the economically profitable potential of recovering and reusing / re-manufacturing end-of-life glass FRP composites.